Improving Early Childhood Language Skills by Telling Stories Using Finger Puppets: A Classroom Action Research - Puspita, Wedya; Kurniawan, Nurhafit (GENIUS: Indonesian Journal of Early Childhood Education, 2024)
Language is a vital tool for human communication. Young children use it to express their thoughts, feelings, and desires. This study aimed to enhance the language skills of Group A students at PKK Ika Karya Bhakti Kindergarten in Probolinggo through storytelling with finger puppets. Employing Classroom Action Research, the researcher sought to address the limited speaking abilities of 13 out of 17 children in pronouncing sentences and recounting personal experiences. The findings demonstrate that the finger puppet approach effectively improved the language skills of these young learners. Specifically, language skills increased from 48% before the intervention to 72.4% after Cycle I and further to 83.8% after Cycle II.  Finger puppets can be a valuable tool for helping young children develop their language skills, especially those who may struggle to express themselves verbally.